Time series forecasting using neural networks without recurrent connections - Masunungure, Takudzwa Trevor (Stellenbosch : Stellenbosch University, 2025)
Masunungure, T. T. 2025. Time series forecasting using neural networks without recurrent connections. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/4fe53217-4ff1-4a6c-9b37-aa467356b164